Digital Tools and Engagement: An Evaluation of Whether Collaborative and Generic Tools can Positively Affect Classroom Culture, Agency and Engagement in Junior Science in a New Zealand Boys' High School - Van den Broek, Peter James (Curtin University, 2021)
This study used a mixed method approach to investigate the impact on engagement resulting from integrating two generic digital tools (Padlet and Flipgrid) into two science classrooms in an all-boys school in New Zealand. The study determined that engagement was improved using these tools although the results for the associated constructs of classroom culture and student agency were less clear.